2022
DOI: 10.3390/v14051086
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response 5–7 Months after Vaccination against SARS-CoV-2 in Elderly Nursing Home Residents in the Czech Republic: Comparison of Three Vaccines

Abstract: Background and Aims: Elderly nursing home residents are especially prone to a severe course of SARS-CoV-2 infection. In this study, we aimed to investigate the complex immune response after vaccination depending on the convalescence status and vaccine. Methods: Sampling took place in September–October 2021. IgG antibodies against spike protein and nucleocapsid protein, the titer of virus neutralization antibodies against delta and (on a subset of patients) omicron, and cellular immunity (interferon-gamma relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Most notable are differences with neutralising antibody (nAb) titres and breadth of neutralisation with hybrid immunity compared to vaccine or infection induced immunity. [28][29][30][31][32][33][34] There are other immunological differences between the groups, including in tissue-resident memory T-cells, and the mucosal immune system, [34][35][36][37] The key strengths of our study include the size of our cohort undergoing frequent PCR testing independent of disease status, giving us confidence that most infections were detected. Having monitored our well-characterised cohort for infections and vaccination since June 2020, we have a valuable history of antigenic exposures for all our participants, enabling analysis of time since infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most notable are differences with neutralising antibody (nAb) titres and breadth of neutralisation with hybrid immunity compared to vaccine or infection induced immunity. [28][29][30][31][32][33][34] There are other immunological differences between the groups, including in tissue-resident memory T-cells, and the mucosal immune system, [34][35][36][37] The key strengths of our study include the size of our cohort undergoing frequent PCR testing independent of disease status, giving us confidence that most infections were detected. Having monitored our well-characterised cohort for infections and vaccination since June 2020, we have a valuable history of antigenic exposures for all our participants, enabling analysis of time since infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most important, recent studies in NH residents with or without a previous history of SARS-CoV-2 infection, have shown higher antibody response ensured by the hybrid immunity effect. Martinek and colleagues showed that 5–7 months after vaccination immune parameters were significantly higher in convalescent residents than in naive residents after vaccination [ 18 ]. Similar findings were described by Jeulin et al who showed that NH residents with a history of SARS-CoV-2 infection have a clear advantage in the magnitude and duration anti-S IgG titers following the 2nd dose [ 19 ].…”
Section: Discussionmentioning
confidence: 99%